Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1093/cercor/bhh031
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory Synchrony in the Monkey Temporal Lobe Correlates with Performance in a Visual Short-term Memory Task

Abstract: Oscillatory synchrony has been proposed to dynamically coordinate distributed neural ensembles, but whether this mechanism is effectively used in neural processing remains controversial. We trained two monkeys to perform a delayed matching-to-sample task using new visual shapes at each trial. Measures of population-activity patterns (cortical field potentials) were obtained from a chronically implanted array of electrodes placed over area V4 and posterior infero-temporal cortex. In correct trials, oscillatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
85
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(96 citation statements)
references
References 54 publications
8
85
0
1
Order By: Relevance
“…The resulting spectral change of the LFP was evident as a decrease in the baseline-normalized beta power and an increase in gamma band power. This effect of visual stimulation causing a shift from high-amplitude, low-frequency activity toward lowamplitude, high-frequency activity has been observed in a large number of studies on visual cortical responses (Gray and Singer, 1989;Taylor et al, 2005;Ray and Maunsell, 2011).…”
Section: Resultsmentioning
confidence: 61%
“…The resulting spectral change of the LFP was evident as a decrease in the baseline-normalized beta power and an increase in gamma band power. This effect of visual stimulation causing a shift from high-amplitude, low-frequency activity toward lowamplitude, high-frequency activity has been observed in a large number of studies on visual cortical responses (Gray and Singer, 1989;Taylor et al, 2005;Ray and Maunsell, 2011).…”
Section: Resultsmentioning
confidence: 61%
“…In ref. 21, this suggestion was shown to be the case for simple auditory tone sequences, and reports showing strong beta1 generation in short-term memory tasks used novel stimuli for each trial (28).…”
Section: Discussionmentioning
confidence: 86%
“…The dynamic signature associated with retention of past stimuli in such sequences appears to involve predominantly the beta1 rhythm. Visual short-term memory tasks reveal strong beta1 activity during retention (28,29), which also correlates with accompanying BOLD responses (30). In addition, working memory impairment is associated with a decrease in phase and coherence measures within the beta1 frequency band (31).…”
Section: Discussionmentioning
confidence: 89%
“…Previous work using a visual attention paradigm in humans (38) and a delayed matching-tosample task in monkeys (39) has suggested that both ␤-band power and ␤-band phase synchronization can be used to predict accuracy of response to stimuli in target discrimination tasks. However, in the present study, we found that neither spectral power nor mutual information between pairs of sensors in the ␤-band significantly predicted performance accuracy (see Figs.…”
Section: Cost Efficiency In Schizophreniamentioning
confidence: 99%